Keberkesanan program akrab terhadap pembangunan pekerja dalam kalangan kakitangan sokongan di Institut Pendidikan Guru Kampus Pendidikan Islam, Bangi - Mohamad Hussin, Mohamad Arsyad (2017)
This study was conducted to identify the effectiveness of AKRAB programme towards employee development among support staff at the Institute of Islamic Education Teacher Education campus in Bangi. This study used a qualitative method based on the phenomenological method and case studies through interviews that conducted among eight respondents. The instrument used was a semi-structured interview that focuses on four dimensions of CIPP Stufflebeam Model which are the dimension of context, input, process and product. The findings show that for dimension of context, participants had set goals and readiness to join from the beginning of the current program. In terms of dimension of input, participants showed high satisfaction with the used of modules, learning methods, ease of training places provided, equipment and materials provided and facilitator who runs the program. In terms of dimension of process, methods of dissemination of information, organizational support, monitoring system and the problems faced during the programs are effective. In terms of dimension of product, the findings also show that this program is highly impact on the transfer of knowledge and skills in the workplace. Meanwhile the impact on employee development showed significant effects on participants' methods of interaction and guidance. Therefore this study concluded that AKRAB program is important for the employee development among supported staff in IPGKPI. This study suggested that the program should be continued in the future with a focus on improvement for each weakness.